Collaborative Optimization Decision of Distribution Network Reconfiguration and Maintenance Considering Soft Switching - WANG Jianjun; RU Wei; SHI Guangnan; SU Xiaoyun; WANG Yifei; JIANG Wei (Journal of Harbin University of Science and Technology, 2024)
The characteristics of soft switching grid-connected operation which can improve the power supply elasticity of distribution network and optimize the operation structure of power grid have not been applied. A collaborative optimization method for distribution network reconfiguration maintenance considering intelligent soft switching is proposed. A distribution network reconfiguration model with the objective of minimizing network loss is established. Considering the maintenance cost and operation cost, the collaborative optimization decision model and solution method of distribution network reconfiguration and maintenance are established. The improved IEEE 33 system is used for example analysis. The simulation results show that the average network loss of the system is reduced by 35. 57 % and the overall voltage deviation of the system is reduced by 17. 2 % after the collaborative optimization of reconfiguration and maintenance. It is verified that the collaborative optimization of distribution network reconfiguration and maintenance considering intelligent soft switching can effectively improve the economy and safety of distribution network operation.